Induction of labor versus expectant management after successful external cephalic version. Issue 4 (14th October 2019) - Barbash‐Hazan, Shiri; Nattiv, Noga; Salzer‐Sheelo, Liat; Bergel, Riki; Hadar, Eran; Osovsky, Micky; Shmueli, Anat
Abstract: Background: External cephalic version (ECV) is a common procedure for women carrying a breech‐presenting fetus, in an effort to avoid a cesarean birth. The benefit of immediate labor induction after ECV vs. expectant management is undetermined. We aimed to evaluate whether induction of labor immediately after a successful ECV improves the chances of a vaginal delivery compared with expectant management. Methods: Retrospective analysis of 296 women who underwent successful ECV performed in term singleton gestations (2007‐2018) in the Rabin Medical Center. Mode of delivery and other obstetrical and neonatal outcomes were compared between women undergoing immediate labor induction after ECV and those managed expectantly. Results: Of 296 women after successful ECVs, 54 (18.2%) underwent immediate labor induction and 242 (81.8%) were managed expectantly. Immediate induction was associated with higher parity (2.4 vs 1.7, P = .03) and lower mean birthweight (3128 vs 3346 g, P < .01). Mode of delivery was similar between groups, and no other significant differences in obstetrical and neonatal adverse outcomes were noted. Discussion: In our cohort, immediate labor induction after successful ECV apparently had no benefits in terms of obstetrical or neonatal complications, and did not reduce the risk of cesarean birth. Therefore, expectant management seems reasonable and safe.